Coaching effectiveness : lessons from reality - Henriques, Paulo Lopes (2022)
This work, based on a questionnaire to 319 coachers of the firms in Portugal, aims to help increase knowledge about the factors underlying the success of coachers. Four factors were identified: “Relationship”, “Preparation”, “Scope of Knowledge” and “Common Behavior” (independent variables) and as dependent the “direct performance” and “perception of performance”. Results revealed a surprise: the low importance attached to Scope of Knowledge in coaching for the success of coachers. They also demonstrate the greater relative importance of “preparation” in explaining the dependent variable, and a high goodness of fit for models presented. Another discovery within this data was that the coach performance is better with male coachers, with more years of experience and with more years in school (master or PhD.). Finally this data seems to indicate that the number of coachees have significant impact on the performance of the coach